Proton‐pumping rhodopsins are abundantly expressed by microbial eukaryotes in a high‐Arctic fjord - Anna Vader; Haywood D. Laughinghouse; Colin Griffiths; Kjetill S. Jakobsen; Tove M. Gabrielsen (Environmental Microbiology, 2018)
Summary Proton‐pumping rhodopsins provide an alternative pathway to photosynthesis by which solar energy can enter the marine food web. Rhodopsin genes are widely found in marine bacteria, also in the Arctic, and were recently reported from several eukaryotic lineages. So far, little is known about rhodopsin expression in Arctic eukaryotes. In this study, we used metatranscriptomics and 18S rDNA tag sequencing to examine the mid‐summer function and composition of marine protists (size 0.45–10 µm) in the high‐Arctic Billefjorden (Spitsbergen), especially focussing on the expression of microbial proton‐pumping rhodopsins. Rhodopsin transcripts were highly abundant, at a level similar to that of genes involved in photosynthesis. Phylogenetic analyses placed the environmental rhodopsins within disparate eukaryotic lineages, including dinoflagellates, stramenopiles, haptophytes and cryptophytes. Sequence comparison indicated the presence of several functional types, including xanthorhodopsins and a eukaryotic clade of proteorhodopsin. Transcripts belonging to the proteorhodopsin clade were also abundant in published metatranscriptomes from other oceanic regions, suggesting a global distribution. The diversity and abundance of rhodopsins show that these light‐driven proton pumps play an important role in Arctic microbial eukaryotes. Understanding this role is imperative to predicting the future of the Arctic marine ecosystem faced by a changing light climate due to diminishing sea‐ice.